2023
DOI: 10.1080/19490976.2023.2178795
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus T6SS2 effector repertoires

Abstract: All strains of the marine bacterium Vibrio parahaemolyticus harbor a type VI secretion system (T6SS) named T6SS2, suggesting that this system plays an important role in the life cycle of this emerging pathogen. Although T6SS2 was recently shown to play a role in interbacterial competition, its effector repertoire remains unknown. Here, we employed proteomics to investigate the T6SS2 secretome of two V. parahaemolyticus strains, and we identified several antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Consistent with this finding, proteins encoded by T6SS1 have elevated DistC, while proteins encoded by T6SS2 have low DistC. Notably, the annotated T6SS2 island appears to be restricted to the T6SS secretion machinery, auxiliary, and regulatory proteins, with identified effector immunity pairs residing outside of the T6SS2 genomic neighborhood ( 66 ). The T6SS2 includes a single hypothetical protein of unknown function (VPA1024).…”
Section: Resultsmentioning
confidence: 72%
“…Consistent with this finding, proteins encoded by T6SS1 have elevated DistC, while proteins encoded by T6SS2 have low DistC. Notably, the annotated T6SS2 island appears to be restricted to the T6SS secretion machinery, auxiliary, and regulatory proteins, with identified effector immunity pairs residing outside of the T6SS2 genomic neighborhood ( 66 ). The T6SS2 includes a single hypothetical protein of unknown function (VPA1024).…”
Section: Resultsmentioning
confidence: 72%
“…Interestingly, in the case of V. parahaemolyticus the checkpoint is reliant on a single conserved effector rather than one of several loaded effectors as observed in the two previous examples [154]. Intriguingly, a single amino acid change in the DUF2345 domain of a VgrG protein from A.…”
Section: The Membrane Complexmentioning
confidence: 93%
“…We and others previously showed that T6SS effector repertoires can be divided into core effectors present in all strains harboring the system and accessory effectors encoded only by a subset of strains [25,58,59]. Therefore, we sought to determine the distribution of CoVes in Vcor genomes.…”
Section: T6ss2 Effectors Are Differentially Distributed In Vibrio Cor...mentioning
confidence: 99%
“…Identifying effector homologs in Vibrio coralliilyticus genomes: BLASTP was employed to identify homologs of the T6SS2 effectors in Vcor genomes, as described previously [25]. The amino acid sequences of new CoVes from strains BAA-450 (WP_006957348.1, WP_006959328.1, WP_006959836.1, WP_006960006.1, WP_006961218.1, WP_006961766.1, WP_006962231.1, and WP_006962597.1) and OCN008 (WP_141650583.1) were used as queries.…”
Section: Identifying T6ss Gene Clusters In Vibrio Coralliilyticusmentioning
confidence: 99%